Peningkatan Literasi Digital Masyarakat Kelurahan Keputran Kecamatan Tegalsari Melalui Pengoptimalisasian Penerapan Identitas Kependudukan Digital (IKD) - Ayu Sabrina Sugandini; Rachmawati Novaria (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The implementation of Digital Population Identity (IKD) has become an important innovation in an effort to simplify the administrative process and increase access to public services, especially for the people of Keputran Village. However, the success of implementing digital population identity is very dependent on the level of digital literacy of the community. This article explores the role of increasing digital literacy in supporting the implementation of digital population identity in an inclusive and sustainable manner for the people of Keputran Village. By paying attention to the challenges and opportunities related to digital literacy, this article presents several strategies and approaches to improve people's digital understanding and skills in the context of digital population identity (IKD). Through a qualitative approach, training and equal access to technology, it is hoped that all residents of Keputran Subdistrict can feel the benefits of implementing digital population identity without exception. Thus, this article not only strengthens the urgency of increasing digital literacy in facing the digital revolution, but also underlines the importance of aspects of inclusion and equality of access in the transformation process towards more efficient, safe and sustainable public services.